Legal analysis of the urgency of determining the free papua organization (OPM) as a perpetrator of gross human rights violations in Indonesia - Alwathoni, Syaif Hizbulhaq (Dynamics of Politics and Democracy, 2024)
Purpose: This study analyzes the urgency of determining the Free Papua Movement (OPM) as a perpetrator of gross human rights violations in Indonesia from a legal perspective. The main focus is to understand and examine the legal consequences and social impacts of such a determination in enforcing justice and protecting human rights in Indonesia. Research/methodology: The research uses a normative legal research method with a descriptive-analytical approach. It relies on secondary data, including legal literature, laws and regulations, and the opinions of legal experts. Results: The study shows that OPM has committed various acts of violence that violate human rights, such as murder, torture, and kidnapping. Declaring OPM as a perpetrator of gross human rights violations is crucial to uphold the principles of justice and equality before the law, in line with national and international legal standards. Legal action against OPM not only aims to impose sanctions but also functions as a preventive measure to deter similar crimes in the future. Experts in human rights law stress the need for a proportional and effective governmental response to such cases. Conclusion: Determining OPM as a perpetrator of gross human rights violations is a necessary legal step to enforce justice, deter future crimes, and protect human rights in Indonesia. Limitations: The study is limited to secondary data without field verification or empirical assessment of the implementation challenges. Contribution: This research contributes to the development of legal science and offers strategic insights into the legal handling of gross human rights violations in Indonesia.